Epistemologi Pemikiran Mu'tazilah dan Pengaruhnya terhadap Perkembangan Pemikiran Islam di Indonesia - Ellyy Warnisyah Harahap; Ulfah Fadillah; Nislah Nasution; Bagus Prasetyo; Fernando Yahya Sitohang; Ayu Purnama Sari; Mhd Shiddiq Daulay (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This research aims to analyze and understand the epistemology of Mu'tazilah thought and evaluate its influence on the development of Islamic thought in Indonesia. Harun Nasution, a leading contemporary Muslim intellectual, advocates a revival of Mu'tazilite theology, emphasizing its importance in shaping Islamic thought in Indonesia. Harun Nasution emphasized that integrating rationality into Islamic theology is very important to modernize Islam in the broader context of societal modernization. Using qualitative research methods, this research explores historical and contemporary texts to explore Mu'tazilah principles and their adaptation in Indonesian intellectual discourse. The results of this research reveal that the Mu'tazilite emphasis on reason, ethical responsibility, and social justice has influenced modern Islamic thinkers in Indonesia, shaping interpretations of religious texts and responses to contemporary social and political challenges. In conclusion, this research emphasizes the relevance of Mu'tazilah thought in fostering an Islamic discourse that integrates rationality with religious principles in Indonesian society.